Pengaruh Pelayanan Dan Kepercayaan Wajib Pajak Terhadap Peningkatan Pendapatan Asli Daerah Di Era Pandemi Covid -19 Pada Badan Pendapatan Daerah Kabupaten Blitar - Rini Yuniastuti; Abu Talkah (Universitas Islam Kadiri, 2022)
The purpose of this study was to determine the effect of taxpayer service and trust on increasing local revenue in the Covid-19 pandemic era at the Blitar Regency Regional Revenue Agency simultaneously and partially. The population in this study are all people who are submitting changes to the SPPT, either mutations, splits and objections at the Service Counter. The sample used in this study was 99 respondents. The method used in this research is multiple linear regression analysis technique. The results of the study show that 1) There is an effect of service and trust on increasing Regional Original Income in the Era of the Covid-19 Pandemic at the Regional Revenue Agency of Blitar Regency simultaneously; 2) There is no effect of service on increasing Regional Original Income in the Covid-19 Pandemic Era at the Blitar Regency Regional Revenue Agency partially. The lack of PAD revenue is still considered an obstacle and this must immediately be seriously evaluated by each local government in an effort to improve services and facilitation to the community. In fact, the lack of effective and efficient targets to achieve the reality of meeting community needs is one of the things that has become the root of the problem of the lack of achievement of regional income so far; 3) There is a partial effect of trust in increasing Regional Original Income in the Covid-19 Pandemic Era at the Regional Revenue Agency of Blitar Regency.